Getting the most out of MRI in perianal fistula: update on surgical techniques and radiological features that define surgical options. Issue 10 (October 2021) - Iqbal, N.; Tozer, P.J.; Fletcher, J.; Lightner, A.L.; Sackitey, C.; Corr, A.; Patel, U.; Ilangovan, R.; Lung, P.
Abstract : Perianal fistulas affect approximately 2 in 10, 000 people, causing symptoms such as pain and discharge, which can have a debilitating effect on a patient's quality of life. Surgical treatment, which can offer a potential cure or palliation of symptoms, must be considered carefully in cases with extensive sphincter involvement. In complex cases, the use of preoperative magnetic resonance imaging (MRI) can help to determine the best course of operative action. This review describes common and contemporary surgical procedures for perianal fistula, highlighting technical features, as well as important surgical considerations associated with each method and how these can be assessed radiologically. We focus on the anatomical features and MRI findings that take procedural elements into account and help determine the most appropriate method of treatment. The aim of this article is to provide a basis for informed and focused discussion between surgeons and radiologists to ensure the most appropriate procedure is selected for each case, with the ultimate aim of obtaining the most favourable outcomes for patients.